Factors influencing carbon emissions in Indonesia : Dynamic model approach - Nano Prawoto; Agus Tri Basuki (Institute of Computer Science (IOCS), 2023)
This study aims to determine the relationship between GRDP growth, Gross Fixed Capital Formation, trade value, added value of the industrial sector and energy consumption to increasing carbon dioxide emissions in Indonesia. The secondary data used for research comes from World Development Indicators, the Indonesian Central Bureau of Statistics, and regional financial reports for the period 1988-2020. The analytical tool used in this study uses the Error Correction Model regression to analyze short-term and long-term relationships between research variables. The results of the study show that in the long term GDRP growth, industrial added value, and energy consumption are the main drivers of increasing carbon dioxide emissions in Indonesia. In the short term, growth in GDRP and consumption of petroleum are driving increased carbon dioxide emissions. The government must be firm with the Presidential Regulation concerning the Application of Carbon Economic Value to Achieve Nationally Determined Contribution Targets and Control of Greenhouse Gas Emissions in National Development. The basic principles and strategies that the government must pay attention to are reducing emissions in urban transportation by limiting the number of vehicles that are not roadworthy and diverting fossil energy to electricity.